2020
DOI: 10.1111/dsji.12207
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Roles of Social Presence and Gender Difference in Online Learning

Abstract: Online learning has become more popular in higher education with its advantages of flexibility and accessibility. However, there have been challenges to students’ learning experience in online learning. One critical challenge would be providing interactions between students and instructors as good or effective as in the face‐to‐face environment. However, providing face‐to‐face interactions in online learning is not feasible because students and instructors are not physically present together. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 59 publications
3
46
0
7
Order By: Relevance
“…When exposed to the online learning environment, the students following the academic major “Food Science and Technology” (FS-IONIO) report a lower level of both emotional engagement and human interactions relative to those following the other two academic majors (either Environmental Science at Ionian University or Chemistry at Athens University). This finding could be related with various factors such as the classes’ size differences (Ruthotto et al 2020 ) and the extent of use of interactive technologies (Park & Kim, 2020 ) in each learning community. The much more applied nature of Food Science and Technology relative to the other two majors and/or the possible negative attitudes of the academic personnel of the specific science department towards the online learning approach could also be related with the observed low level of emotional engagement (EEO) and human interactions (HUMIO) in the online learning environment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When exposed to the online learning environment, the students following the academic major “Food Science and Technology” (FS-IONIO) report a lower level of both emotional engagement and human interactions relative to those following the other two academic majors (either Environmental Science at Ionian University or Chemistry at Athens University). This finding could be related with various factors such as the classes’ size differences (Ruthotto et al 2020 ) and the extent of use of interactive technologies (Park & Kim, 2020 ) in each learning community. The much more applied nature of Food Science and Technology relative to the other two majors and/or the possible negative attitudes of the academic personnel of the specific science department towards the online learning approach could also be related with the observed low level of emotional engagement (EEO) and human interactions (HUMIO) in the online learning environment.…”
Section: Discussionmentioning
confidence: 96%
“…The higher mean level of the traditional relative to the online learning environment applies also to the human interactions factor, with statistically significant differences observed in all four examined learning communities. Although research has shown that students feel greater connection with instructors and their peers in online courses when instructors use interactive technologies consistently and purposefully (Park & Kim, 2020 ), it seems that the abrupt shift from the traditional face-to-face in-campus education to an online learning environment due to COVID-19 pandemic did not allow the use of technology to its fullest potential.…”
Section: Discussionmentioning
confidence: 99%
“…The term social presence was first defined by Short, Williams, and Christie (1976) as a degree of salience between two communicators. Since then, it has become a part of the debate for reconceptualization with various perspectives in online communication and learning (Park & Kim, 2020). Social presence is considered one of the components of successful online teaching and learning (Park & Kim, 2020).…”
Section: Social Presence and Online Learningmentioning
confidence: 99%
“…Since then, it has become a part of the debate for reconceptualization with various perspectives in online communication and learning (Park & Kim, 2020). Social presence is considered one of the components of successful online teaching and learning (Park & Kim, 2020). Although this term is less operationalized but well understood in the context of the constructivist approach towards learning which describes learning as a social activity, and that individuals learn best when they interact with others for knowledge construction, and meaningful learning (Oztok & Brett, 2011).…”
Section: Social Presence and Online Learningmentioning
confidence: 99%
“…Online learning provides higher education to increase access to and attract students who may not regularly attend campus (Park & Kim, 2020). According (Nguyen, 2015) Online learning is a form of distance learning or distance learning that has long been part of the American educational system and has become the largest distance learning field in recent years.…”
Section: Online Learningmentioning
confidence: 99%